1981
DOI: 10.1007/bf01866821
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bird communities on surface mine lands in Pennsylvania

Abstract: / A variety of species was observed as either visitors, permanent, or summer residents on surface mines with different ecological adaptations. Passerine species were the most prevalent of the 25 families represented. Bird communities as well as individual species were correlated with the structure and species of vegetation on the mines. The composition of the bird communities changed in response to successional vegetation stages from grassland to forest communities.Open-pit or surface mining for coal has destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Other studies have even shown densities to be higher in non-mined areas than mined areas (Brenner & Kelly, 1981;Krementz & Sauer, 1982). Overall richness, or number of species counted in each site, was greater in the mined area than the non-mined area, agreeing with Brenner & Kelly (1981) who observed a change in avian species as the vegetation successional stage changed, therefore increasing species richness on the overall area.on a 20-year-old reclamation site. Bergon et al, (1996) reported that disturbance created by mining and the changes in vegetation structure encourage habitat heterogeneity where new ecological niches are created such as the wetlands and species richness is increased.…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have even shown densities to be higher in non-mined areas than mined areas (Brenner & Kelly, 1981;Krementz & Sauer, 1982). Overall richness, or number of species counted in each site, was greater in the mined area than the non-mined area, agreeing with Brenner & Kelly (1981) who observed a change in avian species as the vegetation successional stage changed, therefore increasing species richness on the overall area.on a 20-year-old reclamation site. Bergon et al, (1996) reported that disturbance created by mining and the changes in vegetation structure encourage habitat heterogeneity where new ecological niches are created such as the wetlands and species richness is increased.…”
Section: Discussionsupporting
confidence: 75%
“…Our results indicate that a manager can direct the natural succession of a reclaimed strip mine or other open area by manipulating the boundary form at the scale of tens of metres. Articulating the boundary into a series of concavities and convexities should accelerate succession, increase patchiness of woody plants, augment the area of edge, enhance wildlife habitat, and increase landscape diversity (McCaffer and Creed 1969, Kimmel and Samuel 1978, Brenner and Kelly 1981, Debussche et al 1982, Romme and Knight 1982, McDonnell and Stiles 1983, Burrows 1984.…”
Section: Management Implicationsmentioning
confidence: 99%
“…In southern West Virginia, Crawford et al (1978) found that the most bird species were found on unmined sites and sites mined 8 years earlier and the highest avian abundance was found on the site mined 9 years earlier. Brenner and Kelly (1981) found that the composition of bird communities changed with successional stages ranging from grassland to forest communities on reclaimed sites. Urbanek and Klimstra (1986) studied bird diversity on surface-mined lands in southern Illinois and concluded that habitat diversity and edge were the most important factors contributing to diversity of bird life.…”
Section: Birdsmentioning
confidence: 99%